Behavior changes to promote preconception health: a systematic review - Maiko Suto; Kimiko Inaoka; Daichi Suzuki; Aya Nitamizu; Naoko Arata; Erika Ota (BMC Women's Health)
Abstract Background Preconception care is expected to prevent diseases, promote health, and improve pregnancy outcomes. Although a consensus exists on the efficacy of folic acid supplementation and preconception vaccination, evidence regarding comprehensive approaches to preconception care targeting the general population remains lacking. We aimed to identify and examine preconception care programs delivered to reproductive-aged women and men to promote behavioral change. Methods We searched the MEDLINE, EMBASE, and CENTRAL databases on November 30, 2023. We included randomized controlled trials (RCTs) and cluster RCTs assessing preconception care programs provided to the general population. We included behavioral change interventions, including screening, counseling, and education, to encourage preconception health. We performed a narrative synthesis of the characteristics and a summary of the intervention effects of the included studies. Results We identified 26 trials (from 29 reports). Most of the studies recruited women. The most common study setting was healthcare services, and various types of behavioral change interventions were noted. All types of interventions, including individual education, group education, online education, and information campaigns, exhibited certain effects of improvement regarding behavioral change, knowledge, health outcomes, and other health-related outcomes in preconception health. Conclusions In this systematic review, only three studies recruited men. Further research on preconception care in men is needed. The topics typically addressed in preconception care are folic acid supplementation and nutrition. Additionally, further research is needed for a comprehensive approach, including physical, mental, and social health. Future research addressing the broad determinants of preconception health for both women and men could provide more effective preconception care.